RANCANG BANGUN APLIKASI ECODUACTION SEBAGAI STRATEGI PENGEMBANGAN KAMPUNG TEMATIK ECO ENZYME BERBASIS SOCIOTECHNOPRENEUR - Dwi Welly Sukma Nirad; Afriyanti Dwi Kartika; Winda Amelia; Salsabila Rahmah; Andrew Kurniawan Vadreas (ITP Press, 2022)
The city of Padang has 11 thematic villages, one of which is the Eco Enzyme Thematic Village, which is held at the Andalas Sepakat Unit Waste Bank office in Andalas Village. The idea of the Eco Enzyme Thematic Village emerged seeing the problem of waste in urban areas, especially the city of Padang which has been piling up in Final Disposal Sites (TPA). In fact, if processed further there is waste that can produce useful products such as processing with Eco Enzyme. However, not many people are able and willing to manage their daily consumption waste into the Eco Enzyme product. The purpose of this research is to facilitate the community in managing waste into Eco Enzyme products to selling finished products and selling the waste itself. This application will consist of 3 excellent features, namely educational features, features for selling Eco Enzyme and waste products (the basic ingredients for Eco Enzyme), as well as interaction features between users so that later they can become an active community to encourage education to the wider community. This application is called the